Haven

2021-01-24

Solve the equation or formula for the variable indicated. $10c-f=-13+cd$, for c

StrycharzT

Subtract cd on both sides.
$10c-f-cd=13+cd-cd$
$10c-f-cd=-13$
$10c-f-cd+f=-13+f$
$10c-cd=f-13$
Use the Distributive Property to factor out c on the left side of the equation
$c\left(10-d\right)=f-13$
Divide both sides by $10-d$.
$c\frac{10-d}{10-d}=\frac{f-13}{10-d}$
$c=\frac{f-13}{10-d}$

xleb123

$c=\frac{-13+f}{10-d}$
Explanation:
Step 1: Move the terms containing $c$ to one side of the equation:
$10c-cd=-13+f$
Step 2: Factor out $c$ on the left side of the equation:
$c\left(10-d\right)=-13+f$
Step 3: Divide both sides of the equation by $\left(10-d\right)$ to solve for $c$:
$c=\frac{-13+f}{10-d}$
Therefore, the solution for $c$ in the equation $10c-f=-13+cd$ is $c=\frac{-13+f}{10-d}$.

Andre BalkonE

Step 1: Move the term containing $c$ to the left side by subtracting $cd$ from both sides of the equation:
$10c-cd-f=-13$
Step 2: Factor out $c$ from the left side:
$c\left(10-d\right)-f=-13$
Step 3: Move the constant term $-f$ to the right side by adding $f$ to both sides of the equation:
$c\left(10-d\right)=-13+f$
Step 4: Divide both sides of the equation by $\left(10-d\right)$ to solve for $c$:
$c=\frac{-13+f}{10-d}$
Therefore, the solution for $c$ in the equation $10c-f=-13+cd$ is:
$c=\frac{-13+f}{10-d}$

Do you have a similar question?